Teaching Learning Javanese News Writing Trough Group Investigation Method And Illustration Media In Senior High School. (December 2019) - Pratisthita, S T; Winarni, R; Sumarwati,
Abstract: The aim of this research was for improving the students' skill of Javanese News Writing in Senior High School student through Group Investigation Method and Illustration media. This research was a classroom action research which conducted in two cycles. One cycle was done in four steps: planning, implementing, observing, and reflecting. The subject of this research was students class X IPS 2 SMA Negeri 1 Jogonalan. The data observations were taken from the teacher, students, and document review. The data collection was done through interview, observation, test, and document review. The data validations used were triangulation technique of data source and triangulation technique. Then, the techniques of analyzing data used were analysis technique and comparative descriptive. This research described that group investigation method and illustration media could improve the quality of process and result from pre-action up to cycle II. The percentage of process quality in pre-action was 22.2%, and then improved to 69, 4%, last in the cycle II the percentage improved to 83.3%. Whereas, the percentage of result quality in pre-action showed 41.6%, and then improved to 58, 3%, last, in the cycle II the percentage improved to 86, 1%. Based on the data explanation above, it can be concluded that group investigation method and illustration media can improve the students' Javanese News Writing Skill on Senior High School Student.